Designing a Diverse, Future-Oriented Vision for Undergraduate Psychology in Australia : Final Investigation Report. - Cranney, Jacquelyn; Provost, Stephen; Katsikitis, Mary; Martin, Frances; White, Fiona; Cohen, Lynne (Australian Learning and Teaching Council (ALTC), 2008)
Final report from an investigation that provided a collaborative framework for the development and articulation of graduate attributes for psychology; research and application of evidence- based teaching in psychology; and the creation of a diverse, future-oriented vision for undergraduate psychology education. A significant outcome has been the development of an agreed set of graduate attributes for psychology, incorporated into the Australian Psychology Accreditation Council's Rules and Standards (APAC, 2008). A resource to support academics wishing to embed graduate attributes in their programs has been initiated, and the extension of graduate attributes to postgraduate psychology education and training is being pursued by team members. Team members promoted and disseminated information regarding evidence-based teaching through a wide variety of forums. A document outlining a possible vision for undergraduate teaching in psychology, and strategies for its achievement, has been tabled for consideration with the peak professional bodies involved in the investigation partnership, the APS and HODSPA.